Rare case of nasolacrimal duct opening into face - Bibhuti Bhusan Nayak; Nilamani Mohanty; Annada Prasad Patnaik (Indian Journal of Plastic Surgery)
Congenital anomaly of nasolacrimal duct is mostly obstructive in nature or is seen in oblique facial clefts. Nasolacrimal duct drain into the inferior meatus in the nose in a normally developed face. We report a rare case of aberrant opening of distal end of nasolacrimal duct into the external skin lateral to the ala of nose in an adult patient. The only case reported so far was in an infant. The patient is a 22 year young male presenting with an opening lateral to the left ala of nose with recurrent discharge and conjunctivitis of left eye. The embryology is also discussed.